Topological and Hyper Topological Coindices of Benzenoid Circumcoronene Series - Yousef, Walid; Alameri, Abdu; Alsharafi, Mohammed; Al-Naggar, Noman; Al-Fuhaid, Belal (Baghdad Science Journal, 2024)
Numerous applications in chemistry are enabled by chemical graph theory, which is a branch of graph theory. Numerical quantities derived from the chemical graphs of a molecule, known as topological indices and co-indices, are used to model the chemical and physical properties of molecules in quantitative Structure-Property relationships (QSPR) and quantitative structure-activity relationships (QSAR) research. Fortunately, chemical-based experiments have found a strong connection between Topological descriptors (topological indices and co-indices) of molecular structures and their Physicochemical Properties, such as boiling point, and toxicity of drugs. Although several research reports have contributed to the computation of topological indices of the benzenoid circumcoronene series, studies on the calculation of topological co-indices are limited. This paper focuses on some topological co-indices. Several formulas of topological co-indices such as first Zagreb, second Zagreb, forgotten, and Yemen co-indices have been derived for the benzenoid circumcoronene series. In addition, the paper introduced new topological indices and their co-indices such as Gaza, Quds, and Palestine indices and co-indices and their mathematical formulas of the benzenoid circumcoronene series. Moreover, some algorithms have been built using Python programs to implement the mathematical formulas that are generally derived.